Uwarunkowania organizacji budującej etyczne przedsiębiorstwo (systematyzacja zmiennych) - Antczak, Zbigniew (The Conditioning of an Organization Creating an Ethical Company (Variable Systematization), 2009)
This paper results come from the author’s scientific diagnosing and systematization of the influence of factors - in globalised Polish economy - limiting cultural-ethic’ companies (CSR, Corporate Social Responsibility).
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 42, s. 13-25